Synthesis and Implementation of a Multiport Dual Input-Dual Output Converter for Electric Vehicle Applications - Reddi Khasim Shaik; C. Dhanamjayulu (International Transactions on Electrical Energy Systems)
In recent years, multiport DC-DC converters are seen in a variety of power converter applications in electric vehicles. The design of multiport converter architectures plays a major role in DC microgrids and electric vehicle applications. This research examines a modified multiport converter structure interface with dual inputs and dual outputs used in electric vehicles. The versatility of accommodating energy sources with varying voltage and current nature characteristics is the most notable feature of this converter. During operation, the proposed architecture can offer a boost as well as buck operations at the same time. The suggested dual input-dual output (DIDO) converter is built with fewer components and a simpler control technique which makes it more dependable and the converter is cost-effective. Furthermore, this structure allows the power to flow in both directions making it to be utilized in electric vehicle battery charging during regenerative braking. The converter’s steady-state and dynamic behavior are investigated, and a control strategy for regulating the power flow among the varied input energies is proposed. To develop the suggested converter, a small-signal model is modeled. MATLAB simulation and experimental findings are used for the verification of converter design and validated the performance behavior experimentally using a hardware setup.